Engorde de pollos criollos mejorados alimentados con soya (Glicyne max) en tres tiempos de tostado. - Verduga Chinga, Ider Amauri (2013)
This research was conducted at the Fifth "GRANDCHILDRENS" located at Km 1/2 track Hope - The Orchard Quevedo belongs to the canton of the Province of Los Rios. Its geographical location is 1 ° 2'30'' E. South, 79 ° 27'30'' West longitude and is located 120 m. The field work lasted 90 days. This study has the following objectives a) To determine the feed conversion, consumption, weight gain and mortality in each of the treatments. B) Set the fastest time in the roasting of soybeans for chicken feed Creoles improved. c) Conduct an economic analysis: Cost / Benefit of the systems used. In the present study we used a completely randomized design (CRD) with four treatments of 3, 6, 9 minutes of roasting soy, experimental measurements, food intake (g), weight gain (g), feed conversion (g), carcass yield (%), mortality, economic analysis. The result in the assessment of roasted soybeans, the greatest weight reported T3 (6 minute roasted soybeans) in the first and second stage and 4123.83 g 1616.67, and the witness had the lowest weight 3714.43 g and 1510.00, In the variable weight gain shows a statistical difference, the best response was recorded by birds that consumed soy toast for 6 minutes with 1572.23, 2507.17 and 4079.40 g, the Creole chickens improved did not differ statistically evaluated in the phase variable and total consumption of food, the birds fed the soy inclusion tostada for 6 minutes and reported average 13468.19 3340.92, 9827.27, g................................